A single-center retrospective analysis of autoimmune glial fibrillary acidic protein astrocytopathy with seizures in children - Fang, Hongjun; Hu, Wenjing; Jiang, Zhi (Frontiers in Neurology, 2025)
ObjectiveWe herein described the clinical characteristics of autoimmune glial fibrillary acidic protein astrocytopathy (GFAP-A) patients with epileptic seizures in the disease course.MethodsA single-center retrospective analysis of autoimmune GFAP-A with seizures was conducted.ResultsThere were 14 patients (35.9%, 14/39) with seizures among 39 pediatric GFAP-A patients, nine were boys and five were girls. Nine patients (64.3%, 9/14) manifested focal seizures, four (28.6%, 4/14) showed generalized tonic–clonic seizures, one (7.1%, 1/14) exhibited both forms, and five (35.7%, 5/14) manifested status epilepticus. In addition to seizures, clinical presentations included fever (71.4%), disorders of consciousness (71.4%), dyskinesia (42.9%), psychiatric symptoms (35.7%), headache (28.6%), and involuntary movements (28.6%). Electroencephalograms were all abnormal during the acute phase, principally presenting as focal or diffuse slow waves. During the acute phase, the control rate of epilepsy with immunotherapy was 50%, and seven patients still needed to be treated with antiseizure medication. After 2 years and 6 months to 4 years and 6 months of follow-up, we observed seven patients (50%, 7/14) with recurrence of seizures at 0.5–15 months after discharge, seven patients were treated with one or more antiseizure medications. Epileptic seizures were ultimately controlled in two patients, seizures diminished in one patient, treatment was ineffective in three patients, and one patient died.ConclusionGFAP-A is an important cause of epileptic seizures in children and immunotherapy plays a crucial role. Several patients experienced chronic epileptic seizures after the acute phase and require long-term antiseizure medication, with a few showing refractory characteristics.